Highly active and selective AlSBA-15 catalysts for the vapor phase tert-butylation of phenol - Vinu, A.; Devassy, Biju M.; Halligudi, Shivaraj B.; Bohlmann, W.; Hartmann, Martin (Applied Catalysis A-General, 2005)
Hexagonally ordered mesoporous AISBA-15 catalysts having n(Si)/(nA]) ratios from 7 to 215 have been synthesized hydrothermally using a cheap non-ionic block copolymer as the structure-directing agent. The obtained materials were analyzed by XRD and nitrogen adsorption to determine the structural order and the textural properties. It has been observed by Al-27 MAS NMR spectroscopy that aluminum atoms are exclusively in tetrahedral coordination for all samples except AISBA-15(7), where octahedral aluminum has been detected to some extent. Temperature-programmed desorption of pyridine showed that AISBA-15(45) has a higher number of strong acid sites as compared to other mesoporous materials such as FeMCM-41, AIMCM-41 and FcAlMCM-41. The catalyst AlSBA-15(45)showed superior performance in the acid-catalyzed tertiary butylation of phenol employing tert-butanol as the alkylation agent. A high phenol conversion of 86.3% is observed for this catalyst at a reaction temperature of 150 degrees C. Over AISBA-15(45), the 4-TBP yield amounts to 40.5% and the 2,4-DTBP yield corresponds to 37.9%. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Acidity; AlSBA-15; aluminum incorporation; butylation of phenol; SBA-15